Clinical applications of benign tumor resection of accessory parotid gland through transoral approach: A report of 5 cases - WANG Qixiao; YIN Xuelai (Kouqiang hemian waike zazhi)
[Objective:] To explore the indications, surgical methods, and curative effects of transoral resection of accessory parotid gland benign tumors, and to improve the level of diagnosis and treatment. [Methods:] The clinical features, imaging manifestations and treatment course of 5 patients diagnosed with accessory parotid gland tumor visited in the department of Oral and Maxillofacial-Head and Neck Oncology, Shanghai Ninth People's Hospital Affiliated to Shanghai Jiao Tong University School of Medicine were retrospectively analyzed. [Results:] All the 5 cases underwent complete resection of the accessory parotid gland mass through transoral approach. Two weeks, 3 months and 6 months follow-up indicated that the patient's intraoral wound healed well, and there were no symptoms of parotid duct injury or facial nerve injury. [Conclusion:] The transoral approach is more suitable for benign tumors with wide range of motion, clear boundary, and no adhesion to the surrounding tissue. The treatment effect is satisfactory and facial incision scar can be avoided. This operating method has good cosmetic effect and high patient satisfaction.